Corporate Governance Factors Affecting Donation: Evidence from Charitable Organizations in Malaysia - Hasnan, Suhaily; Mohamad, Maslinawati; Zainuddin, Zairul Nurshazana; Abidin, Zubaidah Zainal (International Journal of Economics and Financial Issues, 2016)
Charitable organizations are involved in activities of common concern to members and donors, but which normally benefit people beyond that membership. The survival of these organizations depends on donors and funders. The main objective of this study is to identify governance factors that affect donation. We posit that there are five governance factors related to donation. The governance factors are the board size, board members having professional qualification, board members with political connections, frequency of meeting, and website availability. Based on a sample of 98 charitable organizations, we found that the governance factors such as board members having professional affiliation and board members with political connections are significantly associated to donation received by the charitable organizations. Keywords: Corporate Governance, Donation, Charitable, Non-profit Organizations JEL Classifications: M10, M14